2020
DOI: 10.3390/su12083199
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Pricing in Recycling and Remanufacturing in Uncertain Environments

Abstract: With the increasing awareness of environmental protection, firms pay much more attention to the recycling and remanufacturing of used products. This paper addresses the problem of the optimal pricing in recycling and remanufacturing in uncertain environments. We consider two strategies of remanufacturing products, by which a recycled product can be repaired and sold as a second-hand product or dissembled into materials for production of new products according to its quality. As the market demand for products a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Table 1 delineates the key distinctions between our study and the literature above. Teunter and Flapper [10] Yan, Ni, and Yang [11] Guo and Ya [12] El and Jaber [13] Ferguson [14] Cai et al [15] Örsdemir et al [16] Chang et al [17] Fahimnia [18] Guo et al [19] Mohajeri and Fallah [20] Luo et al [21] Yu et al [22] Xie and Ma [23] Hong et al [24] Wang et al [25] Chai et al [26] Fang and Zhao [27] Zhang et al [28] Our proposal…”
Section: Literature Reviewmentioning
confidence: 84%
See 1 more Smart Citation
“…Table 1 delineates the key distinctions between our study and the literature above. Teunter and Flapper [10] Yan, Ni, and Yang [11] Guo and Ya [12] El and Jaber [13] Ferguson [14] Cai et al [15] Örsdemir et al [16] Chang et al [17] Fahimnia [18] Guo et al [19] Mohajeri and Fallah [20] Luo et al [21] Yu et al [22] Xie and Ma [23] Hong et al [24] Wang et al [25] Chai et al [26] Fang and Zhao [27] Zhang et al [28] Our proposal…”
Section: Literature Reviewmentioning
confidence: 84%
“…Teunter and Flapper [10] investigated remanufacturing schemes for recyclables with varying quality, assuming that quality conforms to a multinomial distribution. Yan et al [11] focused on determining the optimal pricing strategies for recycling and remanufacturing products in uncertain environments, considering two remanufacturing approaches based on product quality, and employing an uncertain programming model along with crisp equivalent models under specific uncertainty distributions. Guo and Ya [12] devised a recycling model that fully considers the quality of recyclables, offering robust theoretical backing for manufacturers in the manufacturing and remanufacturing production decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Abbey et al [36] studied the optimal pricing of new and remanufactured products on the basis of the consumer preferences model. Yan et al [37] formulated a pricing model for recycling and remanufacturing in uncertain conditions to address the optimal pricing. Additionally, pricing decisions are commonly considered in integration with the production decisions, as the pricing strategies in remanufacturing can be influenced by the product design [14].…”
Section: (A) "Competition" Themementioning
confidence: 99%
“…Whether a component is to be reused or becomes waste depends on its quality. Yan et al [21] demonstrated that a recycled product can be used as a second-hand product, repaired, or dissembled into materials according to its quality. Generally, for companies, the higher the ratio of reusable to disposable components, the greater is the economic profit.…”
Section: Remanufacturingmentioning
confidence: 99%